The Use of Mobile Apps for Islamic Learning: A Study on Accessibility and Learning Outcomes - Ibrahim Umar; Siddik Faruk Tilli (Journal of Computers for Science and Mathematics Learning, 2025)
The integration of mobile applications into Islamic education offers a transformative opportunity to enhance accessibility and foster improved learning outcomes. This study explores the role of mobile apps in Islamic learning, emphasizing their accessibility and impact on students’ educational achievements. Employing a mixed-methods research approach, data were collected through surveys and interviews with students and educators from various Islamic institutions. The collected data were analysed using statistical methods to evaluate the usability and effectiveness of mobile apps in facilitating educational processes. The findings reveal that a substantial majority of students perceive these applications as user-friendly, which directly correlates with notable improvements in learning outcomes, such as enhanced memorization of Qur’anic verses, deeper comprehension of Hadith, and better engagement with Islamic teachings. Additionally, mobile apps proved to be instrumental in bridging gaps in traditional education by providing flexible and accessible learning platforms. Despite these advantages, challenges were identified, including limited availability of high-quality content, insufficient digital literacy among some users, and the need for culturally and pedagogically appropriate app designs. This study underscores the significant potential of mobile apps as complementary tools in Islamic education while highlighting areas for improvement. It calls for collaborative efforts among app developers, educators, and policymakers to address these challenges and enhance the effectiveness of mobile apps in Islamic learning contexts. Recommendations include the development of tailored educational content, increased digital literacy initiatives, and continuous innovation to ensure mobile technology aligns with the values and goals of Islamic education.